CERVICAL CANCER SCREENING AND ASSOCIATED FACTORS AMONG WOMEN OF REPRODUCTIVE AGE IN LHOKSEUMAWE, ACEH - Rahayu, Mulyati Sri; Maulina, Nora; Nadhira, Cut Sidrah; Sawitri, Harvina; Kautsar, Muhammad; Sakinah, Nur (Universitas Airlangga, 2024)
Cervical cancer is the second most prevalent cause of cancer-related mortality among women worldwide. Indonesia has the second-highest incidence of cervical cancer worldwide. The etiology of cervical cancer in women is multifactorial. This study aimed to investigate the Pap smear screening tests and analyze the risk factors associated with cervical cancer in women of reproductive age in Lhokseumawe, Aceh, Indonesia. This quantitative study used a cross-sectional design. The data source comprised secondary data collected between January and September 2023 at a clinical laboratory in Lhokseumawe, Aceh, Indonesia. The study sample consisted of 100 women who underwent the Pap smear test. The independent variables examined were age, age at first childbirth, age at menarche, parity, menstrual cycle, history of contraceptive use, and history of miscarriage, whereas the dependent variable was the Pap smear test results. Chi-square analysis demonstrated significant correlations between miscarriage history (p=0.05), parity (p=0.001), menstrual cycle duration (p=0.049), and Pap smear cytological results. Logistic regression revealed that women with a previous miscarriage, more than two children, and menstrual cycles exceeding 28 days were 3.46, 1.32, and 2.53 times more likely, respectively, to have abnormal Pap smear results. Therefore, high-risk women should undergo regular cervical cancer screening to detect the precancerous lesions.